The Influence of Price and Product Quality on Consumer Purchasing Decisions - Safri Tahir; Muh. Ramli (Pustaka Digital Indonesia, 2025)
The purpose of this study was to determine and analyze whether price and product quality have a significant effect on purchasing decisions at Baleta Outlet. The population in this study are all consumers who bought Baleta Outlet products in Palopo City. The sampling technique in this study used purposive sampling, namely the determination of samples based on the objectives and considerations of researchers and consumers who have purchased Outlet Baleta Palopo City. The data analysis technique in this study used descriptive analysis. The results of this study indicate that price and product quality have a significant effect on consumer purchasing decisions at the Palopo City Outlet Shop. The magnitude of the effect of price and product quality is 89% which influences consumer purchasing decisions at the Baleta Outlet Shop in Palopo City.